Comparative Analysis of Gradient Diffusion and Disk Diffusion with Agar Dilution for Susceptibility Testing of Elizabethkingia anophelis - Chien-Tung Chiu; Chung-Hsu Lai; Yi-Han Huang; Chih-Hui Yang; Jiun-Nong Lin (MDPI AG, 2021)
Elizabethkingia anophelis has recently emerged as a cause of life-threatening infections. This study compared the results of antimicrobial susceptibility testing (AST) conducted for E. anophelis through different methods. E. anophelis isolates collected between January 2005 and June 2019 were examined for their susceptibility to 14 antimicrobial agents by using disk diffusion, gradient diffusion (Etest; bioMérieux S.A., Marcy l'Etoile, France), and agar dilution methods. The agar dilution method was the reference assay. According to the agar dilution method, the isolates exhibited the highest susceptibility to minocycline (100%), doxycycline (97.6%), rifampin (95.2%), and levofloxacin (78.6%). A very major error rate of >1.5% was observed for nine antibiotics tested using the disk diffusion method. The overall categorical agreement rate between the disk diffusion and agar dilution methods was 74.8%, and ceftazidime, minocycline, levofloxacin, and rifampin met the minimum requirements for discrepancy and agreement rates. The Etest method tended to produce lower log2 minimum inhibitory concentrations for the antibiotics, except for trimethoprim-sulfamethoxazole and rifampin; the method resulted in very major errors for nine antibiotics. The overall essential and categorical agreement rates between the Etest and agar dilution methods were 67.3% and 76.1%, respectively. The Etest method demonstrated acceptable discrepancy and agreement rates for ceftazidime, minocycline, doxycycline, levofloxacin, and rifampin. AST results obtained through the disk diffusion and Etest methods for multiple antibiotics differed significantly from those obtained using the agar dilution method. These two assays should not be a routine alternative for AST for E. anophelis.